KMT2A-rearranged diffuse large B-cell lymphoma in a child: a case report and molecular characterization. (20th April 2021) - Kato, Shota; Kubota, Yasuo; Sekiguchi, Masahiro; Watanabe, Kentaro; Shinozaki-Ushiku, Aya; Takita, Junko; Hiwatari, Mitsuteru
Abstract: KMT2A -rearranged diffuse large B-cell lymphoma (DLBCL) is rare in both the adult and pediatric populations, and its biological features are unclear. We here report the case of a 19-month-old female with a right temporal bone tumor that was ultimately diagnosed as DLBCL by tumor biopsy. There was no morphological evidence of bone marrow infiltration at diagnosis. The tumor nearly completely dissolved after scheduled chemotherapy for mature B-cell lymphoma; however, leukemic conversion occurred 2 months after completion of chemotherapy. Additional chemotherapy including hematopoietic cell transplantation in a non-remission state was unsuccessful, and disease progression ultimately resulted in the death of the patient 18 months after the diagnosis. We detected the KMT2A-MLLT3 fused transcript in the bone marrow of the patient with primary and recurrent cancer. RNA-sequencing of the bone marrow with recurrent cancer confirmed the KMT2A-MLLT3 fusion gene, although fusion genes involving BCL6, BCL2, or were not detected. Moreover, RNA-sequencing revealed overexpression of MEIS1 and MEF2C, which are highly expressed in KMT2A -rearranged leukemia, whereas the HOXA gene cluster was not overexpressed. The current case formed part of the KMT2A -rearranged acute lymphoblastic leukemia cluster in a T-distributed stochastic neighbor embedding plot. The aggressive clinical course and RNA-sequencing results of the present case suggest that KMT2A -rearranged DLBCL shares biological features with KMT2A -rearranged leukemia.